Hepatitis-B virus infection in India: Findings from a nationally representative serosurvey, 2017-18. (November 2020) - Murhekar, Manoj V.; Santhosh Kumar, Muthusamy; Kamaraj, P.; Khan, Siraj Ahmed; Allam, Ramesh Reddy; Barde, Pradip; Dwibedi, Bhagirathi; Kanungo, Suman; Mohan, Uday; Mohanty, Suman Sundar; Roy, Subarna; Sagar, Vivek; et al.
Highlights: Our study indicates a low prevalence of chronic hepatitis B virus infection among children in India. A higher proportion of children born after introduction of HB vaccine had serological evidence of HB vaccination compared to those born before vaccine introduction. Of the 906 children aged 5 years, eleven (1.21%) were positive for HBsAg. Abstract: Introduction: India introduced a hepatitis-B (HB) vaccine in the Universal Immunization Program in 2002–2003 on a pilot basis, expanded to ten states in 2007–2008 (phase-1), and the entire country in 2011–2012 (phase-2). We tested sera from a nationally representative serosurvey conducted duing 2017, to estimate the seroprevalence of different markers of HB infection among children aged 5–17 years in India and to assess the impact of vaccination. Methods: We tested sera from 8273 children for different markers of HB infection and estimated weighted age-group specific seroprevalence of children who were chronically infected (HBsAg and anti-HBc positive), and immune due to past infection (anti-HBc positive and HBsAg negative), and having serological evidence of HB vaccination (only anti-HBs positive). We compared the prevalence of serological markers among children born before (aged 11–17 years) and after (aged 5-10 years) introduction of HB-vaccine from phase-1 states. Results: Among children aged 5–8 years, 1.1% were chronic carriers, 5.3% immune due to past infection, and 23.2% vaccinated. The corresponding proportions among children aged 9–17 years were 1.1%, 8.0%, and 12.0%, respectively. In phase-1 states, children aged 5–10 years had a significantly lower prevalence of anti-HBc (4.9% vs. 7.6%, p < 0.001) and higher prevalence of anti-HBs (37.7% vs. 14.7%, p < 0.001) compared to children aged 11–17 years. HBsAg positivity, however, was not different in the two age groups. Conclusions: Children born after the introduction of HB vaccination had a lower prevalence of past HBV infection and a higher prevalence of anti-HBs. The findings of our study could be considered as an interim assessment of the impact of the hepatitis B vaccine introduction in India.